How opposition parties sustain single-party dominance: Lessons from India. (May 2017) - Ziegfeld, Adam; Tudor, Maya
When elections are free and fair, why do some political parties rule for prolonged periods of time? Most explanations for single-party dominance focus on the dominant party's origins, resources, or strategies. In this article, we show how opposition parties can undermine or sustain single-party dominance. Specifically, opposition parties should be central in explaining single-party dominance in countries with highly disproportional electoral systems and a dominant party whose vote share falls short of a popular majority. Employing a quantitative analysis of Indian legislative elections as well as a paired case study, we show that opposition coordination plays a crucial part in undermining single-party dominance.